Application Development of Lecturers Training Need Analysis based on Competencies at Stikom Surabaya - Soemarno, Dewangga Pramananda; Amelia, Tan; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Stikom Surabaya is an educational institution that focus on information technology. The background of IT based institution make Stikom Surabaya require lecturers that fulfill the requirement, Stikom Surabaya should have a standard competence to be met. The problem that happened in Stikom Surabaya is some of the lecturer didn’t fulfill the standard of competence. Because of the problem, Stikom Surabaya need a solution that could help the institution to do some analysis about who should get a training to improve lecturer’s skills and what training should the lecturer got. In this research, the analysis will be done to all lecturer in each department at Stikom Surabaya to do some assessment based on the fact and the standar that developed by institution. Information System and technology is one of the solution that could be done to help to solve the problem and the form of the solution will be an application that will do analysis about development requirement based on competency. Hopefully, because of the help of the application Stikom Surabaya will effectively and efficiently solve the problem. Other than the application that help to analyse, this application will give a report of training requirement for all lecturers.